Eksistensi Karya Kacapi Tunggal Yoyoh Supriatin - Siti Rafa Haniyya (Paraguna, 2022)
Kacapi Tunggal is an art in which the performance only uses the Kacapi musical instrument. It was created by a sinden named Yoyoh Supriatin with different Kacapi picking patterns and is the hallmark of this Kacapi Tunggal art. This study aims to see the existence of a Kacapi Tunggal in modern society. The research method used in this study is a qualitative method, by observing the community and producing descriptive data in writing. Based on the data collected, it can be concluded that the existence of the Kacapi Tunggal Yoyoh Supriatin began to be displaced by the number of foreign arts entering Indonesia.